Journalistic Message in Commercial Communication: Program-length Commercials in Generalist Radio Stations - Muela-Molina, Clara; Perelló-Oliver, Salvador (Estudios sobre el Mensaje Periodístico, 2017)
The present work explores the use of program-length commercials defined as a modality of hybrid message that combines commercial and journalistic contents, in most cases introduced by the journalist himself with no explicit forewarning to listeners. In order to respond to the issues that have been raised in this paper, the study has analysed all program-length commercials broadcast in generalist radio stations. These practices, in breach of advertising legislations and the code of ethics of the sector, do not distinguish editorial contents from advertising and exploit the credibility of journalists as opinion leaders to promote a product or service, with a lack of respect to audiences and the consent of radio owners.
Keywords: Radio; advertising; information; journalist; regulation; ethics